Deteksi Hemaglutinin, Hemolisin dan Koagulase Secara Fenotipik dan Genotipik pada Staphylococcus aureus Isolat Asal Broiler - Khusnan Khusnan; Dwi Kusmanto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2018)
Staphylococcus aureus is a bacterium causing diseases in animals and human. Staphylococcus aureus in broilers cause septicemia, tendosinovitis, dermatitis, endocarditis, wound infections, arthritis and bumblefoot. In this research, 24 isolates of Staphylococcus aureus from broiler were characterized of its virulent factors including the presence of haemagglutinin, ability to agulate the plasma in tubular coagulase test as well presipitate formation in clumping factor test, and haemolysis types. By polymerase chain reaction (PCR) were genotypically detected genes coa, clf, hlaA, and hlaB. All of the isolates (100%) had haemagglutinin, capable to agglutinate and precipitae of rabbit plasma. All isolates could lyse sheep red blood cells with the type of α-hemolysis (45.8%), β-hemolysis (50.0%) and γ-haemolysis (4.2%). Genotypically, all isolates (100%) had coa and clf genes, hlaA gene 7(0.8%) and hlaB gene (29.2%).